Enantioselective synthesis of (+)‐(S)‐laudanosine and (-)‐(S)‐xylopinine - Mujahidin, Didin; Doye, Sven (European journal of organic chemistry, 2005)
Abstract: The study presents a new pathway for the enantioselective synthesis of benzylisoquinoline alkaloids. The key steps of the synthesis of (+)-(S)-laudanosine (1) and (-)-(S)-xylopinine (2) are a Sonogashira coupling that builds up the C1-C8a bond of the benzylisoquinoline skeleton, an intramolecular Ti-catalyzed hydroamination of an alkyne, and a subsequent enantioselective imine reduction according to Noyori's protocol.